1981
DOI: 10.3168/jds.s0022-0302(81)82730-0
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Environmental Influences on Milk and Milk Component Production

Abstract: Estimates of genetic parameters and environmental correlations were from deviations from modified contemporary average of standardized records of first lactations of Holsteins in Pennsylvania. Records were extended to 305 days and adjusted for month of calving prior to calculation of deviations. Heritabilities from intrasire correlations among paternal sisters were .23, .26, .22, .71, and .64 for yields of milk, fat, and protein, and percentages of fat and protein. Genetic correlations were positive and genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
8
2
1

Year Published

1987
1987
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 15 publications
8
8
2
1
Order By: Relevance
“…The two data sets gave such similar results that later individual herds, groups of three, groups of six, and the complete set (herds 1 to 24) were analyzed separately relations between milk and protein are more similar from study to study than correlations between milk and fat (4,11,15,16,27). The greater heritabilities in this study may be due to the tendency shown in many studies [e.g., (7)] for heritability to increase with herd production, which is much greater in these data than in data used in earlier studies.…”
Section: Resultssupporting
confidence: 52%
See 1 more Smart Citation
“…The two data sets gave such similar results that later individual herds, groups of three, groups of six, and the complete set (herds 1 to 24) were analyzed separately relations between milk and protein are more similar from study to study than correlations between milk and fat (4,11,15,16,27). The greater heritabilities in this study may be due to the tendency shown in many studies [e.g., (7)] for heritability to increase with herd production, which is much greater in these data than in data used in earlier studies.…”
Section: Resultssupporting
confidence: 52%
“…Because the data resulted mostly from daughters of proved bulls, heritability estimates might have been reduced because of selection. Hargrove et al (11). using differences from modified contemporary averages and method 1 of Henderson (12), reported estimates similar to those of Lawlor (15).…”
Section: Introductionsupporting
confidence: 69%
“…Also they found that some ofthe relationships were nearer to zero for the 3 r and later parities, perhaps because of selection bias. Results of the present .study were generally consistent with previous reports (DE JAGER and KENNEDY, 1987;HARGROVE et al, 1981;MAIJALA and HANNA, 1974). WELPER and FREEMAN (1992) found that genetic correlations for the l st lactation of Lc% was -0.30 with MY but the corresponding estimates between MY with F% and P% were also negative but were larger than that found between MY and Lc%.…”
Section: Y=xb+xu+esupporting
confidence: 83%
“…data sets are presented in Table 6. All estimates are moderate and positive values that genetically ranged from .01 to .22 while phenotypically ranged from .04 to .22 and more nearly in agreement with previous works (DE JAGER and KENNEDY, 1987;HARGROVE et al, 1981;MAIJALA and HANNA, 1974). Estimates of L R s that were >0 15 was obtained only for high HF% genes and HF.…”
Section: Correlations Of Scs With Milk Production Within Paritysupporting
confidence: 77%
“…For fat yield and protein yield the heritability estimates are in the range 0.20 to 0.40 [9][10][11][12] . Repeatability estimates of yield traits are high and range from 0.50 to 0.55 6,12 .…”
Section: Introductionmentioning
confidence: 99%